Insights and Trends of Capstone Project of CS/IT Department of Bicol University from 2011 to 2019 - Balilo Jr., Benedicto B.; Rodriguez, Ryan A.; Guerrero, Jonathan Jaime G. (International Journal of Computing Sciences Research, 2023)
Purpose – This study aims to provide a review of the thesis submitted by undergraduate students and provide sound inputs to academic programs which shall open new trends of researchable areas.  This may also influence the research areas of the IT degree program once students started to propose capstone projects.  More importantly, the output of this study shall give faculty members the insights of setting the capstone development projects and encourage them to introduce diverse applications of technology Method – The samples of the study are the manuscript Bachelor of Science in Information Technology (BSIT) obtained from 2011 to 2019 with capstone details (i.e. name of a student, capstone titles, adviser, panel members).  These manuscripts are extracted from the CSIT faculty department, faculty storage room, department computer, and main library of the University.  A total of two-hundred seventy-three (273) manuscript titles were retrieved for analysis.  The titles are converted into lowercase characters for easy categorization utilizing the features MS Excel transposition method and PivotTable.  Special symbols like dash, colon, parentheses, slash, and apostrophe are removed to provide a list of common words.  The standard frequency count and categorization of capstone titles were used to count the number of thesis per year, filter and categorized the titles according to keywords.   Results –The study provided sound inputs to academic programs which shall open new trends of researchable areas.  This may also influence the research areas of the IT degree program once students started to propose capstone projects.  On the part of the faculty, the study provided insights into setting the capstone development projects and encourage them to introduce diverse applications of technology research. Conclusion – The study exposed the challenges and opportunities of the BSIT thesis to many possible activities in terms of enrichment or pieces of training, exposure to current technology trends, and policy formulation.  Students' awareness and exposure to various programming languages, database server applications, methodologies, and application types have dramatically changed over time. The proposed research area was geared towards the emerging trends in technology and computer.  The BSIT program followed the suggested and recommended capstone project titles stipulated in the CHED Memo Order of 2012 and #25 series of 2015.  The suggested capstone titles include software development, multimedia system, network design, and implementation, and IT management. Research topics are always a challenge not just for faculty and students but for the department program as well.  One possible intervention to change the course of future research undertakings is to assess the human resource capability and review the curriculum.  Recommendations – The capstone project titles are inclined to system development.  It is therefore recommended that it is better to encourage new concepts to system development but need to consider and explore the suggested project titles by CHED along with the areas of multimedia, network design and implementation, and IT management which include planning and security strategies.  A follow-up study can be proposed to study the influence factor of students in the selection of programming languages, methodology, framework, and other parameters in implementing a capstone project. Research Implications – Almost all developed capstone projects are inclined to browser-based application development and developed using PHP scripting language.  The inclusion of information like tools and applications (including the versions) used in the development provides a general idea of the process.  Discussion of current trends and potential researchable areas could be presented before the capstone project proposal.  This would give students insights and probably room for opportunity to expose students to higher learning ability.